Desenvolvimento de método empregando microextração líquido-líquido dispersiva em fase reversa para determinação de Na, K, Ca e Mg em biodiesel - Lourenço, Emilene de Carvalho (2016)
This research developed a method for employing reversed-phase dispersive liquid-liquid microextraction (RP-DLLME) as sample preparation for the extraction and pre-concentration of Na, K, Ca and Mg in biodiesel samples. The determination of analytes were executed through flame atomic absorption spectrometry (F AAS), operating in emission mode for Na and K and absorption mode for Ca and Mg. The extraction/pre-concentration step of the analytes was performed using a mixture of two solutions, a dispersing and an extractor, which were added to each sample in appropriate volumes and concentrations. The extraction of analytes occurred after the addition of the dispersing-extractor settled-phase mixture formed via centrifugation. Some parameters were evaluated on the extraction efficiency, such as: sample mass (3, 5, 10 and 20 g), different kinds of dispersant solvent and proportion (isopropanol, 60, 65, 70, 75, 80, 85% (v/v)), concentration of the extraction solution (HNO3 0,5; 1;1,5 and 2 mol L-1 (v/v)), the volume of extraction phase (0.5; 1.0; 1.5 and 2.0 mL), centrifugation time (5, 10 and 15 min) and temperature (45, 55, 65 and 75 °C). All the studied and adjusted parameters were made by analytes addition (1.0 μg) on the samples with two biodiesel multielemental standards (2.5 and 20 μg g-1 Na, K, Ca and Mg) whose results were expressed in recovery percentage (%). Due to the determination of analytes by F AAS, an external calibration was performed with aqueous reference solution. The calibration curves for Na, K, Ca and Mg were linear between 0.1 and 2.0 mg L-1. The quantification limits of Na, K, Ca and Mg for this method were respectively: 0.04; 0.02; 0.05 and 0.08 mg kg-1. The accuracy of the proposed method was assessed by recovery experiments and the values obtained were between 94% and 108% with RSD less than 5% for all analytes. The developed method was then applied to five different samples of biodiesel produced from different raw materials. Hence, the developed method was considered viable for the determination of Na, K, Ca and Mg in biodiesel, in accordance with the requirements of Brazilian regulation, which sets maximum limits of 5 mg k-1 for adding Na and K and the same limit for adding Ca and Mg. The main aspects that characterize this method are its simplicity in operation, low cost, low consumption of reagents according to the principles of green chemistry, easy operation equipment use, high analytical frequency, and low limits of quantification for the determination of analytes for F AAS.